Molecular characterization of the rare translocation t(3;10)(q26;q21) in an acute myeloid leukemia patient - Jancuskova, Tereza; Plachy, Radek; Zemankova, Lucie; Hardekopf, David Warren; Stika, Jiri; Zejskova, Lenka; Praulich, Inka; Kreuzer, Karl-Anton; Rothe, Achim; Othman, Moneeb Ak; Kosyakova, Nadezda; Pekova, Sona (Molecular cytogenetics, 2014)
BACKGROUND: In acute myeloid leukemia (AML), the MDS1 and EVI1 complex locus - MECOM, also known as the ecotropic virus integration site 1 - EVI1, located in band 3q26, can be rearranged with a variety of partner chromosomes and partner genes. Here we report on a 57-year-old female with AML who presented with the rare translocation t(3;10)(q26;q21) involving the MECOM gene. Our aim was to identify the fusion partner on chromosome 10q21 and to characterize the precise nucleotide sequence of the chromosomal breakpoint. METHODS: Cytogenetic and molecular-cytogenetic techniques, chromosome microdissection, next generation sequencing, long-range PCR and direct Sanger sequencing were used to map the chromosomal translocation. RESULTS: Using a combination of cytogenetic and molecular approaches, we mapped the t(3;10)(q26;q21) to the single nucleotide level, revealing a fusion of the MECOM gene (3q26.2) and C10orf107 (10q21.2). CONCLUSIONS: The approach described here opens up new possibilities in characterizing acquired as well as congenital chromosomal aberrations. In addition, DNA sequences of chromosomal breakpoints may be a useful tool for unique molecular minimal residual disease target identification in acute leukemia patients.
Keywords: MECOM; Molecular marker; AML; Chromosomal microdissection; Next-generation sequencing